A fundamental study of chromium deposition and poisoning at cathodes of solid oxide fuel cells - Chen, Xinbing (2011)
Intermediate-temperature solid oxide fuel cells (IT-SOFCs) have received considerable attention due to the improved stability, reliability and reduced cost compared with high temperature solid oxide fuel cells (HT-SOFCs). One important advantage of IT-SOFCs lies in the use of metallic materials with better properties and lower cost to replace ceramic materials as the interconnect. However, gaseous chromium species will be vaporized from the Cr2O3 oxide layer formed on the most widely used chromia-forming alloys under SOFC working conditions and thus cause the performance degradation of the cathode, i. e., chromium poisoning effects. Fundamental understanding of chromium deposition and poisoning is very important in the development of IT-SOFCs based on metallic interconnect. The objectives of this project are to investigate chromium deposition and poisoning processes at selected cathodes of SOFCs and to develop chromium-tolerant cathodes for metallic-interconnect based SOFCs. (La0.8Sr0.2)0.95(Mn1-xCox)O3±δ (LSMC, 0.0≤x≤1.0) and (La0.6Sr0.4-xBax)(Co0.2Fe0.8)O3-δ (LSBCF, 0.0≤x≤0.4) cathode systems were selected for the systematic study of the chromium deposition and poisoning. In the case of LSMC cathodes, the electrochemical activity of the cathodes for the O2 reduction reaction increased as B-site Mn was substituted by Co due to the increased oxygen exchange coefficient and oxygen diffusion coefficient as a result of the increased oxygen vacancies of the LSMC pervoskite. However, in the presence of the chromia-forming metallic interconnect, the chromium deposition on the electrolyte surface in contact with the LSMC electrode decreased while on the electrode surface it increased as the Co content in LSMC pervoskite increased from 0.0 to 1.0. On the other hand, the chromium poisoning effects as measured by the increase in the overpotential and electrode polarization resistance were most pronounced for the LSMC cathode with x=0.4. The results clearly indicated that the increase in the electrochemical activity of the cathode did not necessarily lead to the reduction in the chromium deposition.